The strength of Japanese companies: a proposed TQM framework using Atlas.Ti - Ahmad, Md. Fauzi; Zakuan, Norhayati; Chin, Thoo Ai; Chan, Shiau Wei; Raja Mohd. Rasi, Raja Zuraidah; Abdul Hamid, Nor Aziati; Abdul Rahman, Nor Aida (Penerbit Universiti Teknikal Malaysia Melaka, 2018)
Total quality management (TQM) has been implemented because of strong global market rivalry. One of Japanese companies' strength is TQM practices. Japanese companies have succeeded in global market mainly due to the effective adoption of TQM practices. It is proved that Japanese companies have dominated in much industry such as electrical and electronic, and automotive. Many previous studies discussed about comparing TQM performs between Japanese and non-Japanese companies. However, most of them were given less emphasis on exploring Japanese TQM strength based on relationship diagram amongst TQM, tools and techniques and business performance, which was identified as the theoretical gap. The main impact of this study is to identify the strength of Japanese companies through relationship diagram based on previous works. Qualitative study has been applied using Atlas.ti and meta-analysis. Based on the result, Japanese companies emphasise in application of tools and techniques and human resource developments in their companies. Tools and techniques have relationship between TQM and business performance to succeed higher impact of TQM practices on their business performance. Finally, authors have proposed a conceptual model for understanding the strength of Japanese companies.